Age- and Sex-Differences in Cardiac Characteristics Determined by Echocardiography in Masters Athletes - Wooten, Savannah V.; Moestl, Stefan; Chilibeck, Phil; Alvero Cruz, José Ramón; Mittag, Uwe; Tank, Jens; Tanaka, Hirofumi; Rittweger, Jörn; Hoffmann, Fabian (Frontiers in Physiology, 2021)
Background: Cardiac function and morphology are known to differ between men and women. Sex differences seen with echocardiography have not been studied systematically in masters athletes. Purpose: To evaluate sex differences in cardiac structure, function and left ventricular (LV) systolic global longitudinal strain among masters athletes. Methods: This cross-sectional study comprises of 163 masters athletes (M=109, 60±12years; F=55, 57±12 years, range 36-91 years) who participated at the 23rd World Masters Athletics Championship held in Málaga, Spain. All athletes underwent state-of-the-art echocardiography including cardiac function, morphology, strain and hemodynamic assessment. Results: LV mass was higher in male than in female athletes (174±44 vs. 141±36 g, p<0.01) due to greater end-diastolic intraventricular septal, LV posterior wall and LV basal diameter. However, LV mass index did not differ between the groups. End-diastolic LV volume and right ventricular area, both indexed to body-surface-area, were greater in men than in women (52.8±11.0 vs. 46.1±8.5 ml/m², p<0.01, 9.5±2.4 vs. 8.1±1.7 cm²/m², p<0.01). In contrast, women had higher LV systolic global longitudinal strain (-20.2±2.6 vs. -18.8±2.6%, p<0.01) and LV outflow tract flow velocity (75.1±11.1 vs. 71.2±11.1 cm/s, p=0.04). Systolic and diastolic blood pressure, LV ejection fraction, and stroke volume index were not different between sexes. Conclusion: Cardiac sex differences are present even among masters athletes. Lifelong exercise training does not appear to exasperate morphological difference to a point of cardiac risk or dysfunction in both male and female athletes.